Exploring characteristics of and transitions between mental states within the Multi-Action Plan model in high-level judo - Kellermann, B.; Collins, D.; MacPherson, A.; Bertollo, M. (European Journal of Sport Science, 2024)
The Multi-Action Plan (MAP) model presents an idiosyncratic framework for human performance. MAP research has categorised four Performance Types (PTs; T1-T4) using self-paced activities. Specifically, T1-4 present four distinct mental states experienced by athletes during performance, differing, among other aspects, in the level of effort and perceived control. However, transitions between PTs are yet to be empirically investigated. This study aimed to examine MAP in the hyperdynamic open-skill combat context of judo. We explored how judoka experienced PTs and the transition processes between these mental states. Six British, high-level judoka (n = 6; Mdnage = 19) were interviewed using a retrospective semi-structured interview schedule. Interpretative phenomenological analysis indicated that judo presents a hyperdynamic difficult-to-predict performance context due to the opponent and fighting rhythm. Second, participants strongly related to T2 and T3 and less to T1 and T4. They also reported experiences `between` T2 and T3. Lastly, participants reported common transition pathways (e.g., T2-T3), typical transition cues, and specific trainable strategies to optimise performance. Findings are discussed in relation to existing literature. Lastly, we present limitations, applied, and research considerations.